The Determinants of Nutritional Status of Workers in Manufacturing Sector - Damayanti, Ratih; Lutfiya , Indah Lutfiya; Noviarmi, Fadilatus Sukma Ika Noviarmi (Public Health of Indonesia, 2024)
Background:The manufacturing industry is a sector that transforms raw materials into finished goods. Nutritional status plays a critical role in determining a worker's productivity, with poor nutritional status often associated with reduced efficiency. Objective:This study aimed to analyze the relationship between various factors and the nutritional status of workers in the manufacturing sector in Surabaya, Indonesia. Methods:This analytical observational study utilized a cross-sectional design. Data collection was conducted from January to March 2023 among manufacturing workers at PT A in Surabaya, East Java Province, Indonesia. Of the total 500 workers, 370 respondents were selected as the study sample. Independent variables included gender, marital status, education level, smoking habits, number of children, exercise habits, contraceptive method usage, and workload level. The dependent variable was nutritional status. Statistical analysis was performed using the Spearman correlation test and the contingency coefficient correlation test to evaluate the relationships between variables. Results:The majority of workers at PT A were male, had a high school education, were married, had 1–2 children, did not use contraceptive methods, were non-smokers, exercised infrequently, and had a moderate physical workload. Significant associations were found between nutritional status and variables such as gender, marital status, contraceptive method usage, smoking habits, and workload level. However, no significant relationships were observed between nutritional status and educational background or the number of children. Conclusion:Among the factors examined, workload level demonstrated the strongest association with nutritional status, likely due to its direct impact on the physical activity required during job tasks. This finding highlights the importance of considering workload in strategies aimed at improving workers' nutritional health. Keywords:determinants; nutritional status; workforce; manufacturing industry